RF Energy Harvesting Study Using Various Metamaterial Patch Structure - M. S. Zainudin; M. K. A. Rahim; N. A. Samsuri; H. A. Majid (Institute of Advanced Engineering and Science, 2017)
The E-field absorbance performance of various metamaterial absorber structure is presented. The study started from the simulation of various design patch of metamaterial absorber. The performances are measured from the reflection coefficient, percentage of absorption, value of E-field and the surface current for circle, square and hexagon patch design of metamaterial absorber. From the simulation, it is shown that the circle patch design shows the most reliable design for harvest energy with the absorption of 99.85% and highest E-field concentration of 2.07 × 105 V/m.